An Overview of In Vitro Models of Alcohol‐Related Hepatocellular Carcinoma - Anoïsia Courtois; Sophie Gérard; Damien Esparteiro; Eric Nguyen‐Khac; Ingrid Marcq; Grégory Fouquet (Cancer Medicine)
ABSTRACT Background Chronic and excessive alcohol consumption is the leading cause of death due to chronic liver disease. Alcohol‐related liver disease (ALD) encompasses a broad spectrum of clinical and pathological features, ranging from asymptomatic and reversible pathologies to hepatocellular carcinoma (HCC), a highly prevalent and deadly liver cancer. Indeed, alcohol consumption is one of the main worldwide etiologies of HCC. However, the impact of alcohol consumption on HCC pathophysiology and the associated mechanisms remains unclear. Thus, in vitro alcohol‐related HCC models are essential for addressing this issue and for assessing new molecular markers of this disease. In this review, we discuss the current in vitro models of alcohol‐related HCC. Our global overview demonstrates the lack of uniformity regarding HCC cell lines, alcohol concentration, and duration of alcohol exposure among existing models. Despite efforts to model alcohol exposure effectively that demonstrate enhancement of cancer cell transformation markers and HCC aggressiveness following, respectively, short‐term and long‐term alcohol exposure, current in vitro models possess numerous limitations. Aim This review highlights future challenges in the development of more integrated and representative models of the complex pathophysiology of alcohol‐related HCC.